STUDI KITAB TAFSIR AL-MUNIR KARYA WAHBAH AL-ZUHAILI DAN CONTOH PENAFSIRANNYA TENTANG PERNIKAHAN BEDA AGAMA - Baihaki, Baihaki (Analisis: Jurnal Studi Keislaman, 2016)
In this article, the author discusses one of the recent literature of Qur’anic exegesis, Tafsir al-Munir fi al-‘Aqidah wa al- Syari’at wa al-Manhaj or better known as Tafsir al-Munir, written by Wahbah al-Zuhaili (1932-2015 AD). In this work, he tried to reach a compromise between classical interpretation with a contemporary one, this is due to some contemporary views that classical account is no longer able to solve the recent problems. Therefore al-Zuhaili tried to integrate classical interpretation to the contemporary style with a consistent method. To find some pictures of his exegesis, the author discusses the verses on interfaith marriage, between Muslims and non-Muslims as an example. This theme is chosen because of its controversy among Islamic scholars and legal experts. In addition to al-Zuhaili’s background as a scholar with special expertise in the field of fiqh (Islamic jurisprudence).